"It was a disaster for us:" 15 years of farming in the shadow of Bumbuna Dam - Stevick, Katherine, author; Luna, Jessie, advisor; Raynolds, Laura, committee member; Hausermann, Heidi, committee member (Colorado State University. Libraries, 2024)
This thesis draws on interviews, participatory mapping, and participant observation in Kalanthuba chiefdom, Sierra Leone, to explore how Limba farmers in Kadala and Kamathor villages understand life with Bumbuna Dam 15 years after its construction. In the first chapter, I argue that the government of Sierra Leone (GoSL) and its industry partner, WeBuild, have taken Limba farmers' land and abandoned the people, leaving them to fend for themselves. Government investment in green energy has transformed villagers into what some anthropologists have termed "surplus populations," who must now scrabble for survival as historic livelihood strategies become increasing untenable. "Surplus" in this context does not imply a neo-Malthusian notion of a population explosion, but rather people who have been left in a vulnerable position half-in and half-out of capitalist economic relations, rather than becoming a fully proletarianized labor force. In the second chapter, I borrow a phrase which recurred throughout my interviews—"sitting in the dark"—to frame how Limba farmers' experience and theorize this half-in, half-out position and experience of abandonment. Villagers use "sitting in the dark" to refer to a figurative lack of education, understanding, and power as well as a literal exclusion from access to electricity. For residents of Kadala and Kamathor, I argue, darkness symbolizes not only exclusion from the material benefits of Bumbuna Dam, but also from modernity as a status with attendant material benefits. Limba leaders' attempts to gain access to electricity for their people, therefore, can be understood as a bid for inclusion in the benefits of green energy development and in the material advantages of being "modern."
It was a disaster for us: 15 years of farming in the shadow of Bumbuna Dam